Chronic Hepatitis C Treatment with Daclatasvir Plus Asunaprevir Does Not Lead to a Decreased Quality of Life - Kawakubo, Megumi (Intern Med, 2018)
OBJECTIVE: The aim of this study was to determine if direct-acting antiviral (DAA) treatment with daclatasvir (DCV) plus asunaprevir (ASV) for 24 weeks influenced the health-related quality of life (HRQOL) at 12 and 24 weeks after treatment initiation [end of treatment (EOT)]. METHODS: This was a prospective, longitudinal study comparing the HRQOL of patients receiving DAA treatment at 12 weeks after treatment initiation and EOT with the HRQOL at baseline. We used a Japanese-validated version of the 8-item Short Form Health Survey (SF-8) to assess the HRQOL of patients. This score can be compared to the Japanese normative sample scores of SF-8. Wilcoxon signed-rank tests were used to compare the HRQOL before treatment, 12 weeks after treatment initiation, and at EOT. PATIENTS: We enrolled patients who received 24-week combination therapy using DCV and ASV for HCV at Saga University Hospital between November 2014 and July 2015. Those who discontinued treatment due to relapse or adverse reactions during the treatment period were excluded from the study. RESULTS: There were no significant changes in any of the SF-8 subscales, Physical component scores (PCS) or mental component scores (MCS) during the treatment period for both males and females. CONCLUSION: Our study makes a significant contribution to the literature because 24-week DAA treatment with DCV plus ASV did not decrease the HRQOL at 12 or 24 weeks after treatment initiation.